2021
DOI: 10.1101/2021.01.08.20248677
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Epidemic waves of COVID-19 in Scotland: a genomic perspective on the impact of the introduction and relaxation of lockdown on SARS-CoV-2

Abstract: The second SARS virus, SARS-CoV-2, emerged in December 2019, and within a month was globally distributed. It was first introduced into Scotland in February 2020 associated with returning travellers and visitors. By March it was circulating in communities across the UK, and to control COVID-19 cases, and prevent overwhelming of the National Health Service (NHS), a ‘lockdown’ was introduced on 23rd March 2020 with a restriction of people’s movements. To augment the public health efforts a large-scale genome epid… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
15
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
3
3
1

Relationship

4
3

Authors

Journals

citations
Cited by 14 publications
(15 citation statements)
references
References 16 publications
0
15
0
Order By: Relevance
“…For the phylodynamic analysis, Scottish ''introduction'' lineages with ten or more sequences were identified (Lycett et al, 2021), and the skygrowth package in R was used to estimate the effective population size over time (using up to ten time intervals), and the growth rates of the lineages within Scotland (Volz and Frost, 2017). The data used for analysis were sampled between Feb 28, 2020 and Aug 18, 2020.…”
Section: Ll Open Accessmentioning
confidence: 99%
“…For the phylodynamic analysis, Scottish ''introduction'' lineages with ten or more sequences were identified (Lycett et al, 2021), and the skygrowth package in R was used to estimate the effective population size over time (using up to ten time intervals), and the growth rates of the lineages within Scotland (Volz and Frost, 2017). The data used for analysis were sampled between Feb 28, 2020 and Aug 18, 2020.…”
Section: Ll Open Accessmentioning
confidence: 99%
“…Our model also estimates the number of individuals with infection in early March, with the most likely case being on the order of 1500 infected individuals in Scotland at this time. While our approach is crude and does not take account of continuing importation of individuals over time, it is substantially greater than the estimate of 113 introductions of COVID-19 into Scotland based on viral sequence data 29 , but is plausible if one takes into account the additional infections these introductions would have caused by the start of our simulations.…”
Section: Discussionmentioning
confidence: 98%
“…A similar pattern of multiple introductions into Scotland was observed for the second wave. Analysis by Lycett et al (12) of sequences available to 21 October 2020, showed that most of the latter were novel lineages, rather than persisting wave one lineages. While some of the wave two lineages were re-introductions from other parts of the UK, the majority were introductions from outside the UK.…”
Section: Date Eventmentioning
confidence: 99%